Time trends of cancer mortality among elderly in Italy, 1970–2008: an observational study - Bidoli, Ettore (BioMed Central, 2012)
BACKGROUND: The aging of the Italian population will unavoidably lead to a growing number of persons diagnosed and living with cancer. A comprehensive description of the burden of cancer mortality among Italian elderly (65-84 years of age) in the last four decades has not been carried out yet. Cancer mortality rates were used to describe time trends between 1970-2008. METHODS: Mortality counts, provided by the Italian National Institute of Statistics, were grouped according to data availability: in quinquennia from 1970-74 through 1995-99, and in 2000-03 and 2006-08 groups. Age-standardized rates (world population) were computed by calendar periods while annual percent changes (APCs) were computed for elderly and middle aged (35-64 years) people for the period 1995-2008. RESULTS: The number of cancer deaths in elderly nearly doubled between 1970-74 (31,400 deaths/year in men, and 24,000 in women) and 2006-08 (63,000 deaths/year in men, and 42,000 in women). Overall cancer mortality rates peaked during the quinquennia 1985-89 and 1990-94 (about 1,500/100,000 in men and 680 in women) and declined thereafter. Throughout 1995-2008 cancer mortality rates decreased by -1.6%/year in men and -0.9%/year in women. These decreases were mainly driven by cancers of the stomach, bladder, prostate, and lung (APC = -3.3%, -2.7%, -2.5%, -2.2%, respectively) in men, and by cancers of the stomach, bladder, and breast (APC = -3.5%, -1.9%, -1.1%, respectively) in women. Conversely, increases in mortality rates between 1995 and 2008 were recorded for lung cancer (APC = +0.6%) in women, cutaneous melanoma (APC = +1.7%) in men, and pancreatic cancer (APC = +0.6% in men and +0.9% in women). CONCLUSIONS: Overall favorable trends in cancer mortality were observed among Italian elderly between 1995 and 2008. Early diagnosis, improved efficacy of anti-cancer treatments and management of comorbidities are the most likely explanations of these positive observations. However, enduring preventive interventions against the most common risk factor (e.g. cigarette smoking), early diagnosis, and access to care should be reconsidered and extended to match the reductions of cancer mortality recorded in the elderly with those in the middle aged.